Nurses’ perspectives on workplace environment needs associated to resilience: a qualitative descriptive study - Li, Meng; Zhao, Runze; Wei, Junfan; Zhou, Linghan; Yang, Shuhua; Tian, Yuan; Wang, Lingning; Zhang, Wenling; Xiong, Xiaoyun; Huang, Chuzhen; Pan, Zhongjie; Song, Ruipeng (Frontiers in Psychiatry, 2024)
Objective: The purpose of this study was to explore the demands of nurses on the workplace environment related to psychological resilience. Methods: A qualitative descriptive design was employed for this study. Purposeful sampling was chosen from a tertiary hospital in Henan Province, China. Semi-structured in-depth interviews were conducted with 20 nurses. The interview data was analyzed using the Colaizzi's method and results were reported following the COREQ standards. Results: Analysis of the interview data revealed three main themes: (1) Career Support & Development, (2) Practical Support & Development, and (3) Personal Support & Development. Conclusion: The perspectives of nurses for a workplace environment demands needs to be appreciated, and in addition, it is worth noting that the key role of building a good workplace environment in strengthening the resilience of nurses emphasizes the need for careful consideration. Nursing administrators should formulate policies and measures from multiple perspectives based on the real needs of nurses in terms of professional, practical, and personal dimensions.